Three new species of the Indo-Pacific stingfish genus Minous (Synanceiidae: Minoinae) with redescriptions of M. trachycephalus (Bleeker 1855) and M. pictus Günther 1880 - Matsunuma, Mizuki; Motomura, Hiroyuki (Zootaxa, 2018)
Three new species of Minous (Synanceiidae: Minoinae) are described. Minous roseus sp. nov., based on 13 specimens from northwestern Australia and the Maldives, is characterized by the following combination of characters: usually XI, 11 dorsal-fin rays; usually II, 9 anal-fin rays; head depth 18.8–21.6% (mean 20.0%) of SL; basal portion of pectoral fin inner surface with black stripes radiating along rays on yellow membranes; and largely pinkish or yellowish body. Although Minous groeneveldi sp. nov., based on a single specimen from Bali, Indonesia, resembles M. roseus, the former differs in having blunt anterior and posterior lacrimal spines with both tips canted ventrally, the eye positioned relatively low on the head and relatively dark body coloration. Minous roseus and M. groeneveldi have also been photographed underwater in North Sulawesi. Minous radiatus sp. nov., based on 54 specimens from the northwestern Pacific Ocean, from the South China Sea and Philippines north to Taiwan, has previously been confused with Minous pictus Günther 1880 (now restricted to Australia and New Guinea). However, M. radiatus differs from M. pictus in having a narrower space between the interorbital ridges, shorter pelvic-fin base, and the pectoral fin inner surface largely yellow, with narrow dark stripes along the rays (relatively large, elongate blotches along the rays in M. pictus). Minous pictus was redescribed from 10 specimens, including a newly-designated lectotype. Minous trachycephalus (Bleeker 1855), related to M. roseus and M. groeneveldi, was also redescribed (with a revised diagnosis), based on the holotype and many specimens from the Indo-West Pacific region. In addition, two examples of Minous andriashevi Mandrytsa 1990, collected off Somalia, are recognized as a new record of the species, previously known only from the holotype collected off the Seychelles. A revised key to species of Minous is also provided.